Sistem Pendukung Keputusan Pemilihan Rumah Kost menggunakan Metode Simple Additive Weighting (SAW) - Reza, Muhammad; Ariyani, Lusi; Sarwandianto, Achmad; Barkah, Januar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Housing development is increasing, one of which is boarding houses, due to the many workers or immigrants wanting to work. However, many workers or local immigrants have difficulty in choosing a boarding house due to the many considerations regarding the aspects of cost, facilities, and location, followed by a large number of boarding houses offering different prices, facilities, and locations, which will make workers or immigrants confused in deciding which place to go. they will stay. Decision Support Systems (DSS) are a type with the capability to solve a problem in semi-systematic and unsystematic terms. This decision support system will later be created using the Simple Additive Weighting (SAW) method to solve problems experienced by workers or immigrants. The author's research technique is determining criteria and alternatives, collecting data, carrying out calculations, and ranking alternatives from the calculation results. The research sample was a boarding house in the Kalibata area, Pancoran, South Jakarta. The results of this research are aimed at making it easier for students or migrant workers who need housing according to their criteria.
Keywords: Decision Support System (DSS); Boarding House Selection; Simple Additive Weighting (SAW) Method